Pengembangan kreativitas guru sekolah dasar melalui pelatihan pemanfaatan kain perca - Otang Kurniaman; Dede Permana; Guslinda; Munjiatun; Eva Astuti Mulyani; Shalamat Ramadani; Garda Fathan Nuzulah (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2025)
Teachers’ creativity in developing contextual and low-cost learning media can be enhanced through the use of readily available recycled materials such as fabric scraps (patchwork). This community service program aimed to strengthen elementary school teachers’ creativity in Singingi District, Kuantan Singingi Regency, by training them to design and produce patchwork-based learning media aligned with the Arts, Culture, and Crafts (SBdP) curriculum. The program was implemented in four stages: needs assessment, planning and instrument development, training implementation, and outcome analysis. Twenty teachers from two elementary schools participated in a short lecture, guided discussion on classroom integration, demonstrations, and hands-on group practice. Knowledge gains were measured through a pre-test and post-test, while creativity was assessed using an observation rubric and product documentation. Descriptive analysis showed improved mastery of the material (from 4.00% to 86.00%) and increased variation in the learning media produced, indicating stronger skills in selecting materials, processing patchwork, and designing safe, functional, and attractive media with clearer plans for classroom implementation.